Molecular and functional characterization of voltage-gated sodium channels in human sperm - Cejudo-Román Antonio; Gallardo-Castro Manuel; Fernández-Sánchez Manuel; Ravina Cristina G; Pinto Francisco M; Candenas Luz (BMC, 2009)
Abstract Background We have investigated the expression of voltage-gated sodium channels in human spermatozoa and characterized their role in sperm motility. Methods Freshly ejaculated semen was collected from thirty normozoospermic human donors, with each donor supplying 2 different samples. Reverse transcription-polymerase chain reaction (RT-PCR) and immunofluorescence techniques were used to detect the mRNAs and proteins of interest. Sperm motility was measured by a computer-assisted sperm analysis system (CASA). Cytosolic free calcium was determined by fluorimetry in cells loaded with the fluorescent calcium indicator Fura-2. Results The mRNAs that encode the different Nav alpha subunits (Nav1.1-1.9) were all expressed in capacitated human spermatozoa. The mRNAs of the auxiliary subunits beta1, beta3 and beta4 were also present. Immunofluorescence studies showed that, with the exception of Nav1.1 and Nav1.3, the Nav channel proteins were present in sperm cells and show specific and different sites of localization. Veratridine, a voltage-gated sodium channel activator, caused time- and concentration-dependent increases in progressive sperm motility. In sperm suspensions loaded with Fura-2, veratridine did not modify intracellular free calcium levels. Conclusion This research shows the presence of voltage-gated sodium channels in human sperm and supports a role for these channels in the regulation of mature sperm function.